2011
DOI: 10.1002/dc.21749
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphologic features of advanced lung adenocarcinomas tested for EGFR and KRAS mutations: A retrospective review of 50 cases

Abstract: Associations between bronchioloalveolar carcinoma (BAC), mucinous differentiation, and epidermal growth factor receptor (EGFR) and KRAS mutations have been previously reported in studies of surgical specimens. We present the cytomorphology of lung adenocarcinomas, including metastases that were diagnosed by cytologic methods and the relationship to both EGFR and KRAS mutational status. We retrospectively reviewed the clinical and cytomorphologic features of 50 lung adenocarcinomas that were tested for both EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…In the present study, we found that 10% of the 77 analyzed adenocarcinoma samples harbored EGFR mutations, 35% of which carried KRAS mutations, while 51% of the 54 samples analyzed for KRAS mutations were negative regarding both mutation types. KRAS mutation results were moderately high for the detection of KRAS mutations with cytomorphological features of adenocarcinomas (12,13), but are in accordance with the recently reported prevalence of NSCLC patients with KRAS mutations (27%) detected using COLD-PCR (14) and 36.9% KRAS mutations detected in malignant pleural effusion of lung adenocarcinoma in a Dutch population (15). …”
Section: Discussionsupporting
confidence: 88%
“…In the present study, we found that 10% of the 77 analyzed adenocarcinoma samples harbored EGFR mutations, 35% of which carried KRAS mutations, while 51% of the 54 samples analyzed for KRAS mutations were negative regarding both mutation types. KRAS mutation results were moderately high for the detection of KRAS mutations with cytomorphological features of adenocarcinomas (12,13), but are in accordance with the recently reported prevalence of NSCLC patients with KRAS mutations (27%) detected using COLD-PCR (14) and 36.9% KRAS mutations detected in malignant pleural effusion of lung adenocarcinoma in a Dutch population (15). …”
Section: Discussionsupporting
confidence: 88%
“…Several studies showed an association of KRAS mutations with poor differentiation 27, 33 . KRAS mutations were found to be associated with a solid growth pattern and tumor-infiltrating leukocytes in lung adenocarcinoma 34 , or more likely to invade visceral pleura 32 .…”
Section: Discussionmentioning
confidence: 99%
“…First, several studies showed an association of KRAS mutations with poor differentiation. 22-24 Although there is currently no standardized grading system for lung adenocarcinomas, solid growth pattern is the central parameter in grading of adenocarcinomas system-wide, and it is likely that the presence of solid growth pattern, at least in part, explains the association of KRAS mutations and poor differentiation in those studies. Furthermore, an association of KRAS mutations with a gene expression profile correlating with solid histology was noted in a study by Motoi et al 21 Lastly, an association of KRAS mutations and “tumor islands”, which in turn were associated with solid growth pattern, was recently reported by Onozato et al 31 …”
Section: Discussionmentioning
confidence: 99%
“…17-20 However, mucinous carcinomas account for only a minority of lung adenocarcinomas with KRAS mutations in western populations, 18, 20, 21 and therefore this association is unlikely to explain the distinct clinical characteristics imparted by KRAS mutations. Several prior studies also suggested that KRAS mutations are associated with poor differentiation, 22-24 but this finding has been inconsistent across publications. Furthermore, because grading of lung carcinomas is not well-established, it is not known which morphologic features (growth pattern, cytologic features, necrosis, etc) may have imparted this association.…”
Section: Introductionmentioning
confidence: 95%